Root and tuber crops in Grenada - Buckmire, K.U.; Benjamin, R.L.; Burris, N. (International Center for Tropical Agriculture, 1986)
The situation of sweet potato, cassava, cocoyam, taro, and yams, mainly grown for subsistence in Grenada, is presented. Their supply, cropping systems, yields, production costs and constraints, and the socioeconomic characteristics of the farmers are briefly discussed. The marketing of sweet potato, yams, and aroids is analyzed as well as the government policies related to the support of root crop plant breeding programs.(CIAT)